2020
DOI: 10.1039/d0na00017e
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoclusters cause selective light-driven biochemical catalysis in living nano-biohybrid organisms

Abstract: We describe selective light-driven biochemical catalysis in living nano-biohybrid organisms made from different atomically-precise gold nanoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The high performance of N 2 -to-NH 3 conversion could be attributed to the increased energy-rich NADPH cofactor that was beneficial for the generation of the Calvin cycle intermediate and solid biomass (Wang et al, 2019b), and the significant upregulation of the key nitrogen-fixation genes including the Mo-Fe nitrogenase gene (nifH) and V-Fe nitrogenase gene (vnfG) (Sakpirom et al, 2019). Compared with the CdS SQDs, gold nanoclusters have been confirmed with more excellent light absorption properties and biocompatibility and were used to realize efficient biological N 2 fixation by A. vinelandii (Bertram et al, 2020). It should be noted that the nitrogen-fixing bacteria may use the produced NH 3 as a substrate for their own growth.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The high performance of N 2 -to-NH 3 conversion could be attributed to the increased energy-rich NADPH cofactor that was beneficial for the generation of the Calvin cycle intermediate and solid biomass (Wang et al, 2019b), and the significant upregulation of the key nitrogen-fixation genes including the Mo-Fe nitrogenase gene (nifH) and V-Fe nitrogenase gene (vnfG) (Sakpirom et al, 2019). Compared with the CdS SQDs, gold nanoclusters have been confirmed with more excellent light absorption properties and biocompatibility and were used to realize efficient biological N 2 fixation by A. vinelandii (Bertram et al, 2020). It should be noted that the nitrogen-fixing bacteria may use the produced NH 3 as a substrate for their own growth.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…23 In addition, a culture of A. vinelandii supplemented with gold nanoclusters also functions as a photocatalytic system for NH 3 production. 24 These results demonstrated the possibility of aerobic NH 3 production by the QD−bacteria hybrid system. In order to exploit this hybrid system and achieve the scalable production of NH 3 , it is necessary to obtain an in-depth understanding of the working principle and biohybrid interfaces of the hybrid system; for instance, photoexcited electrons transfer from QDs to the MoFe protein in the whole cell of A. vinelandii, as studied in vitro.…”
Section: ■ Introductionmentioning
confidence: 66%
“…In addition, a culture of A. vinelandii supplemented with gold nanoclusters also functions as a photocatalytic system for NH 3 production . These results demonstrated the possibility of aerobic NH 3 production by the QD–bacteria hybrid system.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The prospects for integrating microbial bioreactions with photosensitive quantum dots (QDs) pose unique synergies for photosynthetic semiconductor biohybrid systems (PSBs), wherein QDs capture light to enhance or modulate biochemical processes in the microbes. − For example, a pioneering study by Sakimoto et al introduced a proof-of-concept PSB system that enhanced CO 2 conversion to biofuel using CdS QDs coupled to Moorella thermoacetica . Ding et al demonstrated the spectral selectivity of this approach by interfacing Azotobacter vinelandii and QDs with size- and composition-tuned absorption spectra and also demonstrated scalability through enhanced biomass production at the gram scale .…”
Section: Introductionmentioning
confidence: 99%